Health Literacy, Health Perception, and Influencing Factors Among Immigrants - Birimoglu Okuyan, Canan; Deveci, Ebru; Karasu, Fatma (UI Scholars Hub, 2025)
Background: Individuals living in rural areas face several healthcare disadvantages, including limited access to medical facilities and specialists during emergencies. This study examines healthy lifestyle behaviors, health perceptions, and influencing factors among immigrants in a rural region of southern Türkiye. Methods: This cross-sectional study involved immigrants registered at a family health center. Data were collected using a sociodemographic questionnaire, the Perception of Health Scale, and the Health Literacy Scale. Results: Statistically significant differences in THLS-32 scores were found based on participants’ occupation, marital status, and education level (p < 0.05). A moderately positive correlation was observed between health literacy and health perception scores (p < 0.05). Conclusions: Research on the relationship between health literacy and health perception among immigrants may offer valuable insights for fostering healthier communities, contribute to the existing literature, and inform rural nursing interventions aimed at addressing negative health perceptions.